Novel GJA1/Cx43 Variant Associated With Oculo-Dento-Digital Dysplasia Syndrome: Clinical Phenotype and Cellular Mechanisms - Sargiannidou, Irene; Christophidou-Anastasiadou, Violetta; Hadjisavvas, Andreas; Tanteles, George A.; Kleopa, Kleopas A. (Frontiers in Genetics, 2021)
Oculodentodigital dysplasia syndrome is associated with numerous pathogenic variants in GJA1, the gene encoding connexin43 gap junction protein. A novel in-frame deletion (p.Lys134del) was found in our clinic. The patient showed all the typical dysmorphic features of the syndrome. The functional consequences of this variant were also studied in an in vitro system. Cells expressed significantly less number of gap junction plaques with a great number of them retained intracellularly.